Pregnancy outcome in low risk pregnancy with decreased amniotic fluid index - Bhat, Swathi; E., Ambika H.; G., Lepakshi B.; S., Savitha C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To evaluate whether oligohydramnios (AFI≤5) has any significance in the outcome of low risk pregnancies. Normal amniotic fluid index in pregnancy is one of the indicators of fetal well-being. In a term pregnancy, oligohydramnios, a condition associated with AFI≤5, could be a sign of placental insufficiency. An association of low AFI with complications like pregnancy induced hypertension, consistently leads to poor fetal outcome. A need to deliver the fetus by cesarean section often arises. Occasionally one comes across a full-term pregnancy with AFI ≤5 with no known high risk factors; this could lead to increased cesarean section rates. Thus, it becomes necessary to evaluate if AFI ≤5 in the absence of other risk factors has any significance on obstetric outcome. Methods: Prospective case controlled study was done. Fifty women with term pregnancies and (AFI≤5) cm not associated with any other high risk factors were enrolled for the study. They were matched with fifty controls with normal AFI. Results: Except for a slight increase in variable deceleration in the study group, no differences were noted with fetal heart rate recordings in NST. Decreased AFI was not associated with increased cesarean section rates, instrumental deliveries or meconium stained amniotic fluid. Severe asphyxia, NICU admission or perinatal mortality was not noted in either group. Conclusions: When a low risk pregnancy is associated with Oligohydramnios (AFI≤5), it does not have any deleterious effect on labor outcome or perinatal outcome.